2013
DOI: 10.1021/cs400141t
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxidation Catalysis Beginning with 2.5 μM [Co4(H2O)2(PW9O34)2]10–: Investigation of the True Electrochemically Driven Catalyst at ≥600 mV Overpotential at a Glassy Carbon Electrode

Abstract: Evidence for the true water oxidation catalyst (WOC) when beginning with the cobalt polyoxometalate [Co4(H2O)2(PW9O34)2]10– (Co4–POM) is investigated at deliberately chosen low polyoxometalate concentrations (2.5 μM) and high electrochemical potentials (≥1.3 V vs Ag/AgCl) in pH 5.8 and 8.0 sodium phosphate electrolyte at a glassy carbon working electrodeconditions which ostensibly favor Co4–POM catalysis if present. Multiple experiments argue against the dominant catalyst being CoO x formed exclusively from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
114
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 67 publications
13
114
0
Order By: Relevance
“…[12][13][14][15][16] We recently demonstrated that three water-soluble Co-porphyrins, CoTPPS, CoTCPP, and CoTMPyP (Figure 1), are all highly active WOCs when using [Ru(bpy) 3 ] 2 + as a photosensitizer and Na 2 S 2 O 8 as a sacrificial electron acceptor; [17] Wang and Groves have also demonstrated that Co-porphyrins are also active as electrocatalysts for WO. [18] In the [Ru(bpy) 3 ] 2 + /Na 2 S 2 O 8 photoinitiated system some degradation of the sensitizer and catalyst cannot be avoided owing to the formation of highly oxidizing sulfate radical anions (SO 4 À C, E 1/2 > 3.15 V vs. NHE).…”
mentioning
confidence: 99%
“…[12][13][14][15][16] We recently demonstrated that three water-soluble Co-porphyrins, CoTPPS, CoTCPP, and CoTMPyP (Figure 1), are all highly active WOCs when using [Ru(bpy) 3 ] 2 + as a photosensitizer and Na 2 S 2 O 8 as a sacrificial electron acceptor; [17] Wang and Groves have also demonstrated that Co-porphyrins are also active as electrocatalysts for WO. [18] In the [Ru(bpy) 3 ] 2 + /Na 2 S 2 O 8 photoinitiated system some degradation of the sensitizer and catalyst cannot be avoided owing to the formation of highly oxidizing sulfate radical anions (SO 4 À C, E 1/2 > 3.15 V vs. NHE).…”
mentioning
confidence: 99%
“…[16,18] Because those dissolved metal anions were catalytically active themselves or prone to form catalytically active species (e.g., CoOx, NiOx), [19] the hydrolytic stability of polyoxometalates should be of major importance. As reported in the literature, polyanions with all-inorganic ligands were robust enough to sustain the harsh oxidizing environment; however, their hydrolytic stability was sometimes questionable and was influenced by many factors (e.g., pH, buffers).…”
Section: Resultsmentioning
confidence: 99%
“…Using ag old electrode and 0.1 m sodium phosphate buffer (pH 8), aT S= 120 mV dec À1 was determined and the value of half-wavep otential (potential at which current reaches 50 %) E 1/2 = 0.750 Vw as found, which is closed to the thermodynamic value for water oxidation (E8 = 0.760 Vv s. RHE, pH 8). [120] The close proximity of the Ru-Ru atoms of the POM was pointed out by the authors as ak ey factor for the electrocatalytic performance, and the results were validated by at est with am ono-substituted Ru-POM, [PW 11 Ru III (H 2 O)O 39 ] 4À ,f irstly synthesized by Pope et al, [108] which had no OER electrocatalytic activity.M ore recently, Stracke andF inke [121,122] tested at etra-Co-substituted POM (Co 4 -POM), [Co 4 (H 2 O) 2 (PW 9 O 34 ) 2 ] 10À ,a sO ER electrocatalyst. This compound had already been reported as an efficient catalyst for the chemical water oxidation [103] and, in this work, the authors found that depending on the reaction conditions (e.g.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…[122] However, the precise distinctionb etween Co 4 -POM or CoO x as dominant catalystw as not attained. [122] Nonetheless, Goberna-Ferrón and co-workers studied the OER activity of [Co 9 (H 2 O) 6 (OH) 3 (HPO 4 ) 2 (PW 9 O 34 ) 3 ] 16À (more stable at ah igh pH than Co 4 -POM), and also verifiedt he formationo faCoO x film on the fluorine-doped tin oxide coated glass electrode, for a POM concentration of 1mm and an applieda nodico verpotential of 1.41 Vv s. RHE. [123] In order to trap free Co 2 + ions and, hence,p reventt he CoO x film deposition, ac helating ligand (2,2'-bipyridyl) was added during the electrolysis experiments.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%